Design of a GSM 900 Energy Harvesting Model for a Remote-Control Device - Deepak Kumar Nayak; Arjuna Muduli (International Journal of Electronics and Telecommunications, 2022)
This paper deals with designing and simulation of an efficient RF-DC energy harvesting system for a remote control device. GSM down-link frequency of 935MHz to 960MHz and uplink frequency of 890MHz to 915MHz is taken as the RF source with centre frequency as 950MHz and 900MHz respectively. The simulation model has been created by using Advanced Design System (ADS) software. Performance of the circuit has been tested with matching and without matching circuits. The output voltage obtained was 0.372V DC and maximum efficiency up to 35.73% was achieved for the downlink GSM frequency by the lumped method for -10dB input source power. By considering more number of rectifier stages, output DC voltage can be increased and it can be utilized for replacing DC battery of the remote control device.